2020
DOI: 10.1037/tra0000429
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative affect in the daily life of world trade center responders with PTSD: An ecological momentary assessment study.

Abstract: The ability to experience positive affect (PA) has clinical and quality of life implications, particularly in vulnerable populations such as trauma-exposed disaster responders. Low PA is included in the diagnostic criteria for posttraumatic stress disorder (PTSD), however evidence for PA reduction in PTSD has been mixed. In contrast, negative affect (NA) has consistently been found to be elevated among individuals with PTSD. Multiday, ecological momentary assessment (EMA) can provide more ecologically valid ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…Also considering evidence that PTS does not coincide with an inability to experience PA per se (Dornbach-Bender et al, 2020 ), it seems that difficulties maintaining PA (occurring later in the emotion-generation time line) is more strongly connected with PTS than difficulties experiencing PA in the first place (occurring earlier in the emotion-generation time line). Speculatively, it is possible that dampening of PA contributes to re-experiencing because it limits the interruption of (and hence strengthens) the activation of images of the negative event on confrontation with event-related cues, contributes to avoidance because it blocks the broadening of (and thus narrows) one’s thought–action repertoire needed to confront situations reminding of the event, and maintains arousal and other signs of hypervigilance by diminishing health-protective biological responses (Dornbach-Bender et al, 2020 ; Tugade & Fredrickson, 2004 ). Future preferably longitudinal research is needed to further examine the linkage of dampening with different symptom clusters of PTS and mechanisms mediating this linkage.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Also considering evidence that PTS does not coincide with an inability to experience PA per se (Dornbach-Bender et al, 2020 ), it seems that difficulties maintaining PA (occurring later in the emotion-generation time line) is more strongly connected with PTS than difficulties experiencing PA in the first place (occurring earlier in the emotion-generation time line). Speculatively, it is possible that dampening of PA contributes to re-experiencing because it limits the interruption of (and hence strengthens) the activation of images of the negative event on confrontation with event-related cues, contributes to avoidance because it blocks the broadening of (and thus narrows) one’s thought–action repertoire needed to confront situations reminding of the event, and maintains arousal and other signs of hypervigilance by diminishing health-protective biological responses (Dornbach-Bender et al, 2020 ; Tugade & Fredrickson, 2004 ). Future preferably longitudinal research is needed to further examine the linkage of dampening with different symptom clusters of PTS and mechanisms mediating this linkage.…”
Section: Discussionmentioning
confidence: 97%
“…PA dysregulation can take various forms; it may occur in processes associated with the emergence of PA (‘antecedent-focused processes’ such as decreased engagement in potentially positive activities) and processes associated with the modulation of emotions (‘response-focused processes’ including non-attendance to, and negative appraisals of positive emotions). Furthermore, PA dysregulation may include both too little upregulation and too much downregulation of PA and may consider stable, trait-like proclivities as well as temporary, state-based responses (Carl et al, 2013 ; Dornbach-Bender et al, 2020 ). Although studies indicated that PTS is not associated with an inability to experience PA per se (Dornbach-Bender et al, 2020 ), there is gradually growing evidence that the dysregulation of PA does contribute to PTS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koch, Liedl, Takano, & Ehring, 2020 ; Pacella, Girard, Wright, Suffoletto, & Callaway, 2018 ; Pfaltz et al, 2010 ) and positive and negative emotions (e.g. Dornbach-Bender et al, 2020 ; Van Voorhees et al, 2018 ). Few studies have investigated health, rather than symptoms, but related topics such as self-esteem and well-being have been explored (Kashdan, Breen, & Julian, 2010 ; Kashdan et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%